The Influence Of Human Resources Competency, Utilization Of Information Technology And Government Intern Control Systems On The Quality Of Regional Financial Reports (Survey On SKPD Kabupaten Bandung Barat) - Ramadhanti, Suci Andini; Rufaedah, Yanti (Indonesian Accounting Research Journal, 2023)
The purpose of this study was to find out how the influence of human resource competence, the use of information technology and the government's internal control system on the quality of regional financial reports. This type of research uses primary data in the form of a questionnaire given to 95 employees of the finance and accounting department of the SKPD in West Bandung Regency. Data analysis used multiple linear regression analysis after testing the validity, reliability and classical assumption tests using SPSS software version 26.0. Secondary data was obtained through books, journals and articles related to this research. The results of this study are that there is a positive and significant influence on Human Resource Competence, Utilization of Information Technology and Government Internal Control Systems partially or simultaneously on the Quality of Regional Government Financial Reports of West Bandung Regency. The R square value of this study is 0.452. This value indicates that 45.2% of the variable Quality of Financial Statements can be explained by the three variables being studied, while the remaining 54.8% can be explained by variables other than these three variables.